Psychometric properties of the WHOQOL-BREF(PT) in a sample of elderly citizens - Goes, Margarida (2021)
The goal of this article was to research the psychometric properties of the WHOQOL-BREF(PT ) instru-ment in a sample of elderly citizens residing in a rural area in their own homes or at family members’ or friends’ homes and to compare the results: (i) to those reported by the team of Portuguese researchers that undertaken the instru-ment’s translation/validation to the Portuguese language and (ii) to those reported internationally by the World Health Organization Quality of Life group. An overall quality of life scoring (QOL24—all facets) is also proposed in this article as novelty. The correlation level between QOL24 and the instrument’s general facet was also investigated.